Optimizing the Quality of Al-Quran Reading through the Management of the Tahsin Extracurricular Program - Siti Musfiroh; Syifa Hanifah Syandra; Bambang Sri Anggoro; Sovia Mas Ayu (Al-Qalam Institue, 2026)
This study aims to analyze the management of Tahsin extracurricular programs in optimizing students’ Qur’anic reading skills. The research focuses on the processes of planning, implementation, evaluation, and the supporting and inhibiting factors influencing program effectiveness. A qualitative descriptive approach was employed. Data were collected through observations, interviews, and documentation involving school leaders, Tahsin instructors, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the management of the Tahsin extracurricular program has been implemented through systematic planning, implementation, and evaluation stages. The program is conducted regularly using talaqqi, drill, and small-group learning methods, which contribute to improvements in students’ Qur’anic reading abilities, particularly in tajwid application, makharij al-huruf accuracy, and reading fluency. Program effectiveness is supported by leadership commitment, teacher competence, student motivation, and a strong religious culture within the school environment. However, limitations in teaching staff, restricted instructional time, and insufficient Qur’anic reading habits at home remain significant challenges. The study implies that effective management of Tahsin extracurricular activities plays a crucial role in enhancing students’ Qur’anic literacy and strengthening a Qur’anic culture within educational institutions.